Environmental management system and its impacts on manufacturing company's performance in Malaysia - Sahrul Alam, Yusoff (2008)
The ways used to limit the environmental liabilities resulting from the utilization of the resources of the environment for wealth creation is through improving the environmental performance of corporations. Therefore, ISO 14001 Environmental Management Systems provides a framework for achieving this goal and would help firms integrate environmental values into their business operations and reduce liabilities. Sceptics think that, overall, EMS will not improve the world's environmental situation because it does not set environmental performance or technology criteria and only give little benefit to the company. This study addressed this as well as other related issues of EMS by using certified manufacturing sector in Malaysia as survey sample. This research was based on EMS implemented companies located throughout Malaysia. Questionnaires were used as the main research instrument. The questionnaire form sent through 3 methods that is telephone survey, e-mail survey and mail survey. This project will study about the benefit of the EMS in economic & environmental, customer satisfaction and impact of EMS implementation to the manufacturing sector in Malaysia. About 59% of company that implemented the EMS do care about the EMS effectiveness and have initiative to develop the potential of EMS. From this study, we can see the EMS not only increase the company performance, but also give alternative in integrating the awareness of environment and indirectly give benefit to the mankind.